Positive school climate and emotional engagement: a mixed methods study of Chinese students as ethnocultural minorities in Malaysian secondary schools - Krauss, Steven; Wong, Emily J. Y.; Zeldin, Shepherd; Kunasegaran, Mageswari; Nga Lay Hui, Janice; Ma’arof, Aini Marina; Yee, Wendy Mei Tien; Ismail, Ismi Arif (SAGE Publications, 2024)
Past research on ethnocultural minority students indicates that persistent inequities require greater attention to the multiple learning supports needed to enhance school success. The present study was designed to extend research in this area by exploring school climate and emotional engagement among minority ethnocultural Chinese students in Malaysian secondary schools. We employed quantitative surveys with 724 students (Mage = 16.1 years; 47.9% female), followed by qualitative interviews with a subset of 25 students (Mage = 16.1 years; 52% female). Path analysis indicated that feelings of safety, socio-emotional support from teachers and peers, and student voice were predictors of emotional engagement for Chinese students, which further predicted cognitive engagement, academic performance, and school behavior. Thematic analysis further revealed that language and communication barriers and bullying negatively impacted students’ sense of safety and engagement. Caring, respectful relationships with teachers led to students having opportunities to direct their own learning and make decisions on schoolwide activities, promoting students’ feelings of engagement. Support from peers increased students’ emotional engagement by reducing school-related stressors. The findings suggest that a mutually respectful, caring school climate and opportunities for student voice can enhance critical school experiences for ethnocultural minority high school students.